STUDI TENTANG NIATAN MENETAP MIGRAN SIRKULER (KASUS MIGRAN SIRKULER ASAL WONOGIRI KE JAKARTA) - Didit Purnomo; Chuzaimah Chuzaimah (Muhammadiyah University Press, 2004)
This aim of the study will analyse factors that influenced intention the migration of the circular migrant. To achieve the aim, this study used the binary logit analysis technique of the Logistics, with made use of the primary data from 100 people who were made the respondent. This model tried to find the model that was best with four scenarios in testing the hypothesis. Results of the analysis showed that the scenario 4 was the best model. The factor that significantly influencedkeniatan resided the migration, he as follows: education (EDUC), and the income in the urban field (INCOME). Results of the prediction from the binary analysis logit the Respondent that said they stayed consistent to continue to become the circular migrant (did not reside) was relatively big, by chance him to reached 92.9%. On the whole the Binary Logit Regression model that was worn to explain factors that influenced niatan resided the circular migrant to this Jakarta had percentage of correct prediction as big as 78%. This at the same time explained that the behaviour the respondents in this research continue to tended as the circular migrant.